2018
DOI: 10.1016/j.stemcr.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

PLAG1 and USF2 Co-regulate Expression of Musashi-2 in Human Hematopoietic Stem and Progenitor Cells

Abstract: SummaryMSI2, which is expressed predominantly in hematopoietic stem and progenitor cells (HSPCs), enforces HSPC expansion when overexpressed and is upregulated in myeloid leukemias, indicating its regulated transcription is critical to balanced self-renewal and leukemia restraint. Despite this, little is understood of the factors that enforce appropriate physiological levels of MSI2 in the blood system. Here, we define a promoter region that reports on endogenous expression of MSI2 and identify USF2 and PLAG1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…and Msi2 (Belew et al, 2018;Voz et al, 2000), were not affected by Plag1 knockdown in neocortical NPCs (data not shown), which may suggest a cell type-or context-dependent function of Plag1. and Msi2 (Belew et al, 2018;Voz et al, 2000), were not affected by Plag1 knockdown in neocortical NPCs (data not shown), which may suggest a cell type-or context-dependent function of Plag1.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…and Msi2 (Belew et al, 2018;Voz et al, 2000), were not affected by Plag1 knockdown in neocortical NPCs (data not shown), which may suggest a cell type-or context-dependent function of Plag1. and Msi2 (Belew et al, 2018;Voz et al, 2000), were not affected by Plag1 knockdown in neocortical NPCs (data not shown), which may suggest a cell type-or context-dependent function of Plag1.…”
mentioning
confidence: 82%
“…and Msi2 (Belew et al, 2018;Voz et al, 2000), were not affected by Plag1 knockdown in neocortical NPCs (data not shown), which may suggest a cell type-or context-dependent function of Plag1. However, as a recent ChIP-seq analysis for Plag1 in hematopoietic cells revealed a novel Plag1 binding motif containing the E-box consensus sequence (Belew et al, 2018), it is possible that genes without the conventional Plag1 motif are also directly targeted by Plag1. However, as a recent ChIP-seq analysis for Plag1 in hematopoietic cells revealed a novel Plag1 binding motif containing the E-box consensus sequence (Belew et al, 2018), it is possible that genes without the conventional Plag1 motif are also directly targeted by Plag1.…”
mentioning
confidence: 82%
See 3 more Smart Citations